2013
DOI: 10.1242/dev.090159
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns of multipotentiality in Ptf1a-expressing cells during pancreas organogenesis and injury-induced facultative restoration

Abstract: SUMMARYPancreatic multipotent progenitor cells (MPCs) produce acinar, endocrine and duct cells during organogenesis, but their existence and location in the mature organ remain contentious. We used inducible lineage-tracing from the MPC-instructive gene Ptf1a to define systematically in mice the switch of Ptf1a + MPCs to unipotent proacinar competence during the secondary transition, their rapid decline during organogenesis, and absence from the mature organ. Between E11.5 and E15.5, we describe tip epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
279
2
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(302 citation statements)
references
References 37 publications
19
279
2
2
Order By: Relevance
“…β cells express pancreatic and duodenal homeobox 1 (Pdx1) and NK6 homeobox 1 (Nkx6.1) (12). Consistently, the Sox9/EGFP + Ins + cells in the GE-treated recipients also expressed Pdx1 and Nkx6.1 (Fig.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…β cells express pancreatic and duodenal homeobox 1 (Pdx1) and NK6 homeobox 1 (Nkx6.1) (12). Consistently, the Sox9/EGFP + Ins + cells in the GE-treated recipients also expressed Pdx1 and Nkx6.1 (Fig.…”
Section: Resultssupporting
confidence: 55%
“…It has been proposed that β-cell neogenesis in adult mice can derive from pancreatic ductal cells (5,6), cells in the islet (7,8), transdifferentiation from glucagon-producing α cells (9,10), or from acinar cells (11)(12)(13). Although it has been consistently reported that pancreatic ductal epithelial cells give rise to insulin-producing β cells during embryonic development (14)(15)(16)(17), whether the pancreatic ductal progenitors can give rise to insulin-producing β cells in neonates and adult mice remains controversial.…”
mentioning
confidence: 99%
“…111,112 Recently, a study described the expression of Ptf1a C MPCs during pancreatic organogenesis. 113 Limited Ptf1a C cells were identified during the secondary transition and later Ptf1a C cells were confined to acinar cells. 113 113 Upon streptozotocin (Stz) administration, acinar trans-differentiation to endocrine/b-cells was enhanced.…”
Section: Sex Determining Region Y Box 17 (Sox 17)mentioning
confidence: 99%
“…113 Limited Ptf1a C cells were identified during the secondary transition and later Ptf1a C cells were confined to acinar cells. 113 113 Upon streptozotocin (Stz) administration, acinar trans-differentiation to endocrine/b-cells was enhanced. 113 Sex determining region Y Box 9 (Sox 9)…”
Section: Sex Determining Region Y Box 17 (Sox 17)mentioning
confidence: 99%
See 1 more Smart Citation